Kajian Pertumbuhan dan Hasil Okra (Abelmoschus esculentus L.) dengan Aplikasi Beberapa Jenis Pupuk Kandang: Study Growth and Yield of Okra (Abelmoschus esculentus L.) with Manure Application - Haryanta, Dwi; Widya, Surya Ari; Aritonang, Erfan Andrianto (Agrocentrum, 2024)
Many livestock waste has not been utilized, and is even left unused, which will harm environmental health. This research aims to determine the effect of types of manure on the growth and yield of Okra plants (Abelmoschus esculantus L.), and to determine the optimum dose of each type of manure as a reference in recommendations for the use of manure for okra plants. . The single factor experiment used a randomized completly block design (RCBD) with 4 treatments repeated 5 times, namely P0 (without drum fertilizer), P1 (cow manure), P2 (chicken manure), and P3 (goat manure). The results of the research showed that cow manure gave the best results even though it was not significantly different from goat manure, with a production of 12.63 tons / hectare, while the smallest effect was even lower than the control, namely the chicken drum manure treatment. In testing manure and compost (solid organic fertilizer) the maturity level must be the same (mature) by looking at the C/N ratio value.